AN ASSESMENT OF HEALTH SYSTEM IN KENYA: TOWARDS THE ACHIEVEMENT OF UNIVERSAL HEALTH COVERAGE - MOGENI, EVANS GEOFFREY; MASESE, GIDEON NYABANDO; MBITHE, POLLYENE MUTUNGA (Machakos University, 2019)
Crude death rates and mortality rates have been high in most of the developing countries due to inaccessibility to health care facilities. For this reason the Kenyan Government, in its bid to realize the universal health care, it has made many changes in the health sector. This study was therefore carried out to assess Kenya’s health system so as to determine its role in the achievement of universal health coverage. While using the desk review approach, the study was carried out between September and December 2018. The main key indicators which were used include; Leadership and Governance, Health Financing, Health Workforce, Medicines and Vaccines, Information Systems and Service Delivery. It was found out that that Kenya has real made a great milestone in most of the key aspects in its journey to realize universal health coverage. Transformational leadership skills have been put into practice and many policies have been formulated and implemented. The number of qualified workforce with necessary skills and experience is increasing and proper guidelines on the use of medicines have been given. It is also worth noting that most of the systems in health facilities have been integrated and this has eased information tracking for patients. The study recommended that if the realization of universal health coverage is going to be a reality, the following need to be done; Increase health budget allocation from the current 7% to 15% as per the Abuja declaration, Align NHIF to UHC which includes; redefinition of NHIF to include Multi- Tier benefit packages, Improve terms of service for medical doctors and Equip public health facilities so that it becomes the best option as opposed to private (Health financing to improve health infrastructure) health facilities.